2006
DOI: 10.1088/0953-4075/39/18/025
|View full text |Cite
|
Sign up to set email alerts
|

Effective atomic numbers and electron densities of some biologically important compounds containing H, C, N and O in the energy range 145–1330 keV

Abstract: A semi-empirical relation which can be used to determine the total attenuation cross sections of samples containing H, C, N and O in the energy range 145–1332 keV has been derived based on the total attenuation cross sections of several sugars, amino acids and fatty acids. The cross sections have been measured by performing transmission experiments in a narrow beam good geometry set-up by employing a high-resolution hyperpure germanium detector at seven energies of biological importance such as 145.4 keV, 279.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 19 publications
6
42
0
1
Order By: Relevance
“…One can easily envisage in the light of earlier results [8,9,21] that, as the incident energy is further increased, this upper limit on Z is only pushed far beyond 9. Although the region 1 < Z ef f < 9 appears very narrow, this is the region which corresponds to the Z ef f of a vast majority of composite materials of biological interest as well as H-, C-, N-and O-based polymers which find wide ranging applications in several fields of science and technology.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…One can easily envisage in the light of earlier results [8,9,21] that, as the incident energy is further increased, this upper limit on Z is only pushed far beyond 9. Although the region 1 < Z ef f < 9 appears very narrow, this is the region which corresponds to the Z ef f of a vast majority of composite materials of biological interest as well as H-, C-, N-and O-based polymers which find wide ranging applications in several fields of science and technology.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent experimental work [9][10][11][12] on the determination of the effective atomic number, Z ef f , we have shown that H-, C-, N-and O-based composite materials such as sugars, aminoacids, fatty acids and several polymer samples behave like pure incoherent scatterers. This aspect is corroborated by the more recent works of Taylor [13] and Manohara et al [14].…”
mentioning
confidence: 99%
“…Several authors have reported the effective atomic numbers for gaseous mixtures (Singh and Badiger, 2012), alcohols (Singh and Badiger, 2013), composite materials (Prasanna et al, 2010), solutions (Kulwant et al, 2001), dosimetric materials (Kiran and Venkata, 1997) and biological materials (Koç and Özyol, 2000;Shivalinge et al, 2005;Manjunathguru and Umesh, 2006;Demir et al, 2012). This study will be helpful for additional information and deciding the appropriate method for computation of the effective atomic numbers analogous to the experimental values.…”
Section: Introductionmentioning
confidence: 86%
“…Onder et al obtained mass attenuation coefficients, effective atomic numbers, and electron densities for TLD compounds [5]. Parthasaradhi et al determined mass attenuation coefficients of tissue equivalent samples in the energy range of 13-44 keV [6].…”
Section: Introductionmentioning
confidence: 99%